1996
DOI: 10.1366/0003702963906573
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR Study of the Electric Field Modulation of Liquid Crystalline 5CB

Abstract: The dynamic IR spectra of electrically modulated liquid crystalline 5CB (4-pentyl-4'-cyanobiphenyl) are determined to be due to the director reorientation. In the absence of dc fields, the IR response is mainly at two times the modulation frequency. IR signals at the modulation frequency may be induced by application of additional dc fields. These signals at the modulation frequency are caused by the creation of polar orientation due to the static field. No difference in dynamic response has been found between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Much research has been conducted on the effects of surface properties on the alignment of liquid crystalline mesophases, ,, and the methods through which specific alignments can be induced, whether textured, chemical, , or other, , are now well established. Even so, the physics of these influences (especially as regards to their impacts on electrooptical dynamics ) remain incompletely understood, and there exist opportunities to exploit new approaches to alignment that might serve as the foundation of a vastly more energy-efficient display technology …”
Section: Introductionmentioning
confidence: 99%
“…Much research has been conducted on the effects of surface properties on the alignment of liquid crystalline mesophases, ,, and the methods through which specific alignments can be induced, whether textured, chemical, , or other, , are now well established. Even so, the physics of these influences (especially as regards to their impacts on electrooptical dynamics ) remain incompletely understood, and there exist opportunities to exploit new approaches to alignment that might serve as the foundation of a vastly more energy-efficient display technology …”
Section: Introductionmentioning
confidence: 99%
“…In the limit t R << 1/Γ, the dynamic response should become distinctly bimodal, exhibiting a driven reorientation in time t R to a non-equilibrium state of internal molecular distortion, which would relax on the much longer time scale 1/Γ. The absence of such effects in our data thus implies its absence in slower experiments, and, indeed, no evidence for internal relaxation is found in several slower experiments [2,20,21]. However, our data appear to be fundamentally inconsistent with earlier observations on 5CB and related molecules at much longer time scales, in which such relaxation is found [7,8,13,14].…”
Section: Discussionmentioning
confidence: 61%
“…50 It has been suggested that the relaxation behavior in different m olecular m oities may not be completely due to different relaxation processes. 22 Another study that employed NMR spectroscopy to examine reorientation effects concluded that the characteristic m olecular relaxation times are independent of the functional group used to determine the director orientation. 51 Due to considerable spectral overlap of the polymer and liquid crystal's vibrational modes, we were only able to determine the temporal response of a few selected m olecular moieties that could be unambiguously assigned to a chemical species.…”
Section: Resultsmentioning
confidence: 99%
“…Events in the reorientation and subsequent relaxation processes occur on time scales ranging, for example, from picoseconds for intra-molecular changes to milliseconds for the rotation of an entire LC m olecule. Both time-and frequency-domain experiments 22 have been widely applied in extracting responses of the LC director to variations in applied potential differences. 23 W hile numerous TR spectroscopic studies have analyzed the m acroscopic dynamic responses of low-molecularweight nematic LCs, 24 the responses of LC molecules in con ned geometries have been less studied.…”
Section: Introductionmentioning
confidence: 99%